Quantification of biomass and energetic value of young natural regenerated stands of Quercus ilex under Mediterranean conditions - Fernandez-Puratich, Harald; Vicente Oliver-Villanueva, Jose (BOSQUE, 2014)
Forest biomass is key to Spain's energy policy. National, regional and local strategies, development programs of management plans and biomass and quantification of the most important species are fundamental. The objective of this research was to quantify and to analyze the calorific value of biomass of holm oak (Quercus ilex subsp. ballota) under Mediterranean conditions. To do this, several natural regenerated plots were selected in the Valencian Community (Eastern Spain). The main obtained results show that the average volume and weight per tree are 0.045 m(3) tree(-1) and 0.033 Mg tree(-1) respectively. In addition, the form factor was determined (0.66). With an average stand density of 3,200 trees ha(-1), the total potential biomass is 105.4 Mg ha(-1). With the results obtained, a function of stem biomass related to the variables DBH (diameter at breast height) and Vf (volume of stem) has been adjusted with significantly high determination level and low estimation errors. This function can be used for the prediction of biomass quantification in natural regenerated holm oak pure stands in the Mediterranean area. Laboratory results show an energetic value of 17.0 MJ kg(-1) biomass. Therefore, the total potential energy is 513 MJ tree(-1) and 1.8 GJ ha(-1). Considering the large forest areas and the potential resources derived from clearings, thinning and fire prevention silvicultural treatments, the holm oak has the aptitude to be considered a valid raw material for energy use (mainly thermal) in Mediterranean rural areas.
The following values have no corresponding Zotero field: pub-location: CASILLA 567, VALDIVIA, 00000, CHILE publisher: UNIV AUSTRAL CHILE, FAC CIENCIAS FORESTALES
Keywords: biomass; energetic value; quantification; Quercus ilex